Delayed versus Accelerated Weight-bearing Rehabilitation Protocol Following Anterior Cruciate Ligament Reconstruction: A Systematic Review and Meta-analysis - Zheyuan Fan; Jingtong Yan; Zhongsheng Zhou; Yu Gao; Jinshuo Tang; Yuhuan Li; Zhuo Zhang; Modi Yang; Jiayin Lv (Medical Journals Sweden, 2022)
Objective: To compare accelerated and delayed weight-bearing rehabilitation of anterior cruciate ligament reconstruction regarding clinical outcome measures of knee function (International Knee Documentation Committee Subjective Knee Form (IKDC), Lysholm Knee Scoring Scale, Tegner Activity Scale, and Knee Injury and Osteoarthritis Outcome Score (KOOS)), knee laxity, range of movement, quadriceps, and bone tunnel enlargement. Design: Systematic review and meta-analysis. Methods: Systematic searches of Embase, MEDLINE, CINAHL, and the Cochrane Library databases, from inception to February 2021, for studies comparing delayed or accelerated weight-bearing rehabilitation protocol after anterior cruciate ligament reconstruction in adult patients. Results: Nine studies met the eligibility criteria. A meta-analysis revealed a higher risk of knee laxity in the accelerated weight-bearing group. Accelerated weight-bearing may be related to higher IKDC scores, while there was no statistical difference for Lysholm, Tegner, and KOOS scores at a follow-up within 2 years. Four of 5 studies reported no statistical difference for quadriceps strength and range of movement scores, while 2 studies reported bone tunnel enlargement in the accelerated weight-bearing group. Conclusion: This systematic review confirmed that accelerated weight-bearing caused more serious knee laxity and bone tunnel widening than delayed weight-bearing after anterior cruciate ligament reconstruction. We therefore recommend that clinicians should select postoperative rehabilitation programmes with caution. LAY ABSTRACT Anterior cruciate ligament rupture is one of the most common sports injuries. This systematic review confirmed that accelerated weight-bearing rehabilitation resulted in more serious knee laxity and bone tunnel widening than delayed weight-bearing rehabilitation after ACLR. We therefore recommend that clinicians should select postoperative rehabilitation programmes with caution.